Nanoparticles in the treatment of chronic lung diseases - Teodora G. Alexescu; Simina Tarmure; Vasile Negrean; Maria Cosnarovici; Victoria M. Ruta; Ionela Popovici; Ioana Para; Mirela G. Perne; Olga H. Orasan; Doina A. Todea (Journal of Mind and Medical Sciences)
Nanoparticles, although considered a topic of modern medicine, actually have an interesting history. Currently, advances in nanomedicine hold great promise as drug carrier systems for sustained release and targeted delivery of diverse therapeutic agents. Nanoparticles can be defined as complex drug carrier systems which incorporate and protect a certain drug or particle. Nanoparticles can be administered via different routes, such as intravenous injection, oral administration, or pulmonary inhalation. Even though the use of nano-carriers via pulmonary inhalation is heavily debated, this system represents an attractive alternative to the intravenous or oral routes, due to the unique anatomical and physiological features of the lungs and the minimal interactions between the targeted site and other organs. Some of the widely used nano-carriers for the treatment of chronic pulmonary diseases, via pulmonary route, are as follows: polymeric nanoparticles, liposomal nano-carriers, solid lipid nanoparticles, and submicron emulsions. Nanocarrier systems provide the advantage of sustained-drug release in the lung tissue resulting in reduced dosing frequency and improved patient compliance. Further studies focusing on understanding the mechanisms of action of nanoparticles and improving their chemical structure are required in order to better understand the potential long-term risk of excipient toxicity and nanoscale carriers.